Antibiotic resistance in aquatic environments: priorities and knowledge for water quality modelling - Jampani, Mahesh; Mateo-Sagasta, Javier; Langan, Simon J. (2023)
Despite urgent global warnings, antimicrobial resistance (AMR) continues to escalate, with projections of 10 million deaths annually by 2050 if unchecked. In response, the International Water Management Institute (IWMI) and partners highlight the environmental dimensions of AMR, particularly the role of aquatic systems in the transmission of antibiotic-resistant bacteria and genes. While AMR has been largely addressed through strategies to curb antibiotic use, this publication emphasizes the critical need to model the environmental pathways of resistance. IWMI’s proposed source-to-receptor water quality modelling framework captures the fate and transport of antimicrobial contaminants through complex water systems, enabling scenario planning and policy guidance. Drawing on field experiences and interdisciplinary research, the framework aims to inform regulatory responses, investment in treatment technologies, and sustainable waste management. The report identifies gaps in environmental data and model calibration, calling for coordinated action across research, institutions, and governments to build resilient, data-driven systems that mitigate the spread of AMR and protect water resources and public health.